PWE-154 The First Evaluation Of The Relationship Between The Chronic Liver Disease Questionnaire And The Eq-5d Index In Hepatic Encephalopathy Patients Treated With Rifaximin-a. (9th June 2014) - Berni, E; Bannister, C; Poole, CD; Conway, P; Nanuwa, K; Currie, CJ
Abstract : Introduction: Estimation of health-related utility is a vital component of the evaluation of relative cost effectiveness of healthcare interventions. The correlation between different measures of quality of life and health related utility in hepatic encephalopathy (HE) has not been explored. The aim of this study was to characterise for the first time the relationship between scores for Chronic Liver Disease Questionnaire (CLDQ) and health-related utility as measured by the EQ-5D index in patients with HE. Methods: Data were available from a phase three trial of rifaximin-α in patients with recurrent HE. Corresponding CLDQ and SF-36 scores were recorded at monthly visits. EQ-5D scores were derived using the SF-36 using a recognised mapping technique. Generalised, linear, mixed modelling methods were used to examine for any association in order to allow for repeated measures. Results: 202 of 299 patients with 920 corresponding observations were included. The average age of the cohort was 57 years and 133 (65.8%) were males with an average baseline MELD score of 13.8. The average time since diagnosis of HE was 25.6 months. Figure 1 illustrates the observed and predicted utility scores derived from CLDQ with an r-squared value of 0.835, indicating a strong relationship. Conclusion: This is the first time that a direct association between the EQ-5D index and the CLDQ score has been reported. The r-squared value of this association suggested that liver-related morbidity may explain the majority of differences in health-related utility in these subjects. Disclosure of Interest: E. Berni Consultant for: Norgine, C. Bannister Consultant for: Norgine;, C. Poole Consultant for: Norgine, P. Conway Employee of: Norgine, K. Nanuwa Employee of: Norgine, C. Currie Consultant for: Norgine.